Complete mitochondrial genome of a cave dwelling Desmopachria (Insecta: Coleoptera: Dytiscidae) from the Eastern Amazon. Issue 2 (1st February 2021) - Vasconcelos, Santelmo; Oliveira, Renato R. M.; Pires, Eder S.; Pietrobon, Thadeu; Prous, Xavier; Asenjo, Angélico; Oliveira, Guilherme
Abstract: Coleoptera presents most of the cave fauna biodiversity, with several troglobite species belonging to the aquatic family Dytiscidae. However, very little is known on both genetic and genomic diversity traits of Neotropical cave beetles. Thus, here we present the complete mitochondrial genome sequence of five specimens of Desmopachria collected in a ferruginous cave from Serra dos Carajás in Parauapebas (Pará, Brazil, Eastern Amazon). Besides the general characteristics of the mitogenome of the analyzed specimens, we present their phylogenetic position within the family, considering the available genome sequences of different subfamilies within Dytiscidae.